Spontaneous poisoning by Ricinus communis leaves (Euphorbiaceae) in goats - Luiz B. Brito; Franklin Riet-Correa; Valdir M. Almeida; Givaldo B. Silva Filho; Hisadora A.S. Chaves; Thaiza C. Braga; Joaquim Evêncio Neto; Fábio S. Mendonça (Pesquisa Veterinária Brasileira)
ABSTRACT: The aim of this study was to report the clinical and pathological aspects of an outbreak of poisoning by the ingestion of Ricinus communis leaves in a herd of goats at Pernambuco, northeastern Brazil. Within 3-5 hours after ingesting the sprouts and young shrubs of the plant, twenty Toggenburg female goats and two adults crossbred wethers presented acute neurological clinical signs, which were initially characterized by decreased locomotor activity that later evolved to severe ataxia, depression, incoordination and staggering gait. Four goat that died spontaneously were necropsied. Gross lesions were unspecific and consisted in focal areas of lungs edema, petechial hemorrhages in the epicardium and congestion and enlargement of liver. The contents of the rumen, reticulum and omasum were dry and contained leaves of the plant. Histologically there were no lesions in the CNS. In the liver, the main lesion consisted in cytoplasmic vacuolization and necrosis of hepatocytes. Eighteen goats recovered after a supportive therapy with activated charcoal, glycated isotonic solution, dexamethasone and vitamin B12. There is no specific therapy for poisoning by R. communis, however supportive and symptomatic treatments are recommended and should be based on the clinical signs.